Determination of laminar flame speed of methaneair flames at subatmospheric conditions using the cone method and ch* emission (2013)
ABSTRACT: Experimental measurements of laminar flame speed for premixed methane-air flames were carried out for different equivalence ratios at subatmospheric conditions, 852 mbar and 298 K. The flames were obtained using a rectangular port burner with a water cooler system necessary to maintain the temperature of the mixture constant. An ICCD camera was used to capture chemiluminescence emitted by OH-CH radicals present in the flame and thus define the flame front. Laminar flame speed was calculated using the cone method and experimental results were compared with those reported by other authors and the numerical simulations made with the software CHEMKIN using the GRIMECH 3.0 mechanism. In this work it was found that decreasing the barometric pressure from 1013 mbar to 852 mbar generated an increase of 7% in the laminar flame speed.